Natural History of Wild-Type Transthyretin Cardiac Amyloidosis and Risk Stratification Using a Novel Staging System - Grogan, Martha; Scott, Christopher G.; Kyle, Robert A.; Zeldenrust, Steven R.; Gertz, Morie A.; Lin, Grace; Klarich, Kyle W.; Miller, Wayne L.; Maleszewski, Joseph J.; Dispenzieri, Angela (Journal of the American College of Cardiology, 2016)
Wild-type transthyretin cardiac amyloidosis (ATTRwt) is increasingly recognized as an important cause of heart failure. The purpose of this study was to determine the natural history of ATTRwt and the predictors of survival. We retrospectively reviewed patients diagnosed with ATTRwt at the Mayo Clinic through 2013 and recorded clinical data and survival data. Factors affecting overall survival (OS) were identified, and a prognostic staging system was developed. The median age of the 360 patients diagnosed before death was 75 years (range: 47 to 94 years), and 91% were male. Presenting signs and symptoms included dyspnea or heart failure in 67% and atrial arrhythmias in 62%. Median OS from diagnosis was 3.6 years and did not change over time. Multivariate predictors of mortality included age, ejection fraction, pericardial effusion, N-terminal pro–B-type natriuretic peptide, and troponin T. A staging system was developed that used thresholds of troponin T (0.05 ng/ml) and N-terminal pro–B-type natriuretic peptide (3,000 pg/ml). The respective 4-year OS estimates were 57%, 42%, and 18% for stage I (both values below cutoff), stage II (one above), and stage III (both above), respectively. Stage III patients were at an increased risk of mortality after adjustment for age and sex compared with stage I patients (hazard ratio: 3.6; p < 0.001). The natural history of ATTRwt is poor. We report a novel cardiac biomarker staging system that enables risk stratification in an era of emerging treatment strategies.